EDUKASI GIZI PEDOMAN GIZI SEIMBANG DAN ISI PIRINGKU PADA ANAK SEKOLAH DASAR NEGERI 06 BATANG ANAI KABUPATEN PADANG PARIAMAN - Hafifatul Auliya Rahmy; Nurul Prativa; Rahmania Andrianus; Mesa Putri Shalma (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Their knowledge of nutrition is one of the causes of indirect malnutrition. Increased knowledge through education nutrition to prevent malnutrition and improve a person's behaviour to consume food according to school-age children's nutrition. Knowledge is one of the factors that influence the attitudes and conduct of one. One promotion of health aimed at increasing knowledge to change someone's attitude is nutrition education about nutrition. SDN 06 Batang Anai from many schools is one of the schools that had received the nutrition assistance programs called